T91. THE POSITIVE AND NEGATIVE SYNDROME SCALE SUPERIOR TO A SELF-REPORT QUESTIONNAIRE IN THE PHARMACOTHERAPY MONITORING AND OUTCOME SURVEY. (18th May 2020) - Bartels-Velthuis, Annegien; Ties, Koen; Visser, Ellen; Arends, Johan; Pijnenborg, Marieke; Wunderink, Lex; Jörg, Frederike; Veling, Wim; Castelein, Stynke; Knegtering, Henderikus; Bruggeman, Richard
Abstract: Background: Aiming to improve the quality of care for patients with a psychotic disorder, the ongoing Pharmacotherapy Monitoring Outcome Survey (PHAMOUS) started in 2006 in four large mental health care organizations in the Northern Netherlands, by adding it to the at that time mandatory Routine Outcome Monitoring program. However, since the cuts in the financial budgets for mental health care, research nurses are increasingly experiencing time-pressure in the assessments. The Positive and Negative Syndrome Scale (PANSS), part of the assessment, is a time-consuming interview, taking approximately 30 minutes. Therefore, we developed and validated a short self-report questionnaire assessing positive psychotic symptoms, the Brief Positive Symptoms Questionnaire (BPSQ). Methods: The BPSQ was added to PHAMOUS and filled in once by patients in four mental health care institutions in 2017 and 2018. The BPSQ consists of nine items and takes about 2–3 minutes to complete. It was validated against the PANSS positive scale and two items of the Health of the Nations Outcome Scale (HoNOS), with item 6 assessing the problems that patients experience due to hallucinations and delusions and item 8 assessing further mental and behavioural problems. Results: BPSQ data were obtained from n=287 patients (mean age 47.1 years, 67.6% male). The PANSS was assessed in n=244 and HoNOS data were available for n=156 patients. Scores of one patient were considered unreliable and thus removed from the data set. The BPSQ had a Cronbach's alpha of .81. Spearman's correlation coefficient of the BPSQ and the PANSS positive scale was significant (ρ(243) = .63, p < .05). Correlations between the BPSQ and HoNOS items 6 and 8 were significant (ρ(155) = .488, p < .05 and ρ(155) = .251, p < .05 respectively). Post hoc analysis showed that the more severely psychotic the patients were, the less the BPSQ and the PANSS positive scale were corresponding. Discussion: Given the medium correlation of the BPSQ with the PANSS positive scale and the low concurrent validity with the two relevant HoNOS items, we argue that the widely used and validated PANSS is indispensable in the PHAMOUS assessment of positive symptoms in a chronic population with psychotic disorders. Replication of this study in first-episode psychotic patients is recommended.